(untitled) (Texas Journal of Medical Science, 2025)
Regular monthly menstrual period is a natural process that occur in female from pubertal stage to certain age before menopause. Delayed menstrual period among female students may pose different health consequences, indicating an underlying cause and this may have impact on both students and their immediate family. These health consequences may hinder students’ academic performance. The aim of this study is Ascertaining the Health Consequences of Delayed Menstrual Period Among Students of Tertiary Institutions on the Family in South-South Nigeria. This was a descriptive study involving 250 female students in tertiary institutions who were within the age of 18 to 47 years. A well-structured questionnaire was administered to participants. Each participant had one questionnaire to fill appropriately and independently after instructions were given to them by the Research Assistants. The study lasted for a period of 3 months (April to June, 2024). Data was analyzed with SPSS version 26 and P value < 0.05 was considered significant. Exclusion criteria were those females who are not student. Inclusion criteria are female students that have attained menarche. Results from the study revealed some of the health consequences of delayed menstrual period observed emanated from hormonal imbalance, stress, pregnancy, nutritional disorders, underlying reproductive issues and being on certain medications. Again, 85% of the students had abortion due to unwanted pregnancy, 65% had PID, 25% ectopic pregnancy, 78% had anaemia from bleeding, 65% experienced pains, 55% experienced sycopal attacks, 75% had irregular menstrual period, 85% had weight gain, and 67% experienced body weakness